La solución pacífica de conflictos en la convivencia escolar de los estudiantes del colegio fiscomisional Leonidas Proaño, en la ciudad de Pujilí en el año lectivo 2015-2016 - Guanoluisa Yánez, Luis Abelardo (2016)
The general objective of this research was to do a training manual about school conflicts. The manual contains specific characteristics, types of conflicts; strategies and methodologies solution, and so on. Helping at Monseñor Leonidas Proaño Educative Unit from Pujilí Canton during the academic period 2015-2016 ". The research problem was how to affect the school conflicts in the learners´ performance? The methodology used was descriptive, field and bibliographic research, which allowed specifying the characteristics of the study problem. The conclusions were: Students suffering a verbal abuse and they do not use conflict resolution strategies and when they do the first alternative is dialogue, parents say that this problem is given by the stage of adolescence. The contribution of this research is to guarantee the school life using guidelines, strategies and activities imposed by the Ministerial the Education the Ecuador. Promoting an alternative to solve inconvenience in student life, giving a useful tool for generating peace and agreements on the educative institution.